2007
DOI: 10.1186/1741-7015-5-11
|View full text |Cite
|
Sign up to set email alerts
|

How to optimise the coverage rate of infant and adult immunisations in Europe

Abstract: Background: Although vaccination has been proved to be a safe, efficacious, and cost-effective intervention, immunisation rates remain suboptimal in many European countries, resulting in poor control of many vaccine-preventable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 31 publications
(45 reference statements)
1
66
0
5
Order By: Relevance
“…55,91,133 For example, results of a large US study indicated that the largest proportion of parents who changed their minds about delaying or not getting a vaccination for their child listed "information or assurances from health care provider" as the main reason. 39 In contrast, the association between use of CAM, such as…”
Section: Health Professionals' Recommendations and Use Of Complementamentioning
confidence: 99%
See 1 more Smart Citation
“…55,91,133 For example, results of a large US study indicated that the largest proportion of parents who changed their minds about delaying or not getting a vaccination for their child listed "information or assurances from health care provider" as the main reason. 39 In contrast, the association between use of CAM, such as…”
Section: Health Professionals' Recommendations and Use Of Complementamentioning
confidence: 99%
“…20,90,91 Health is also a documented barrier to vaccination. For example, results of a study conducted by Taddio and collaborators indicated that about two-thirds of children and one-quarter of parents reported needle fears.…”
Section: The Role Of Health Professionalsmentioning
confidence: 99%
“…Despite the proven safety and efficacy of vaccines, immunisation rates remain suboptimal in many European countries, and some common vaccine-preventable diseases are not controlled to the extent to which they could [1].…”
Section: Knowledge and Perception Towards Vaccinesmentioning
confidence: 99%
“…Their recommendations play an influential role in their patients' vaccination behavior. Their patients perceive them as a reliable source of information about vaccines, [14][15][16] and their consultation can also be a key factor in patients' decision to be vaccinated or not. [17][18][19][20][21] Moreover, their recommendations to patients about vaccinations are associated with their vaccination behaviors and attitudes for themselves.…”
Section: Introductionmentioning
confidence: 99%